2018
DOI: 10.11144/javeriana.umed59-3.cyto
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Plasma Cytokine Levels before and after Treatment with Rituximab in Patients with Rheumatoid Arthritis and Systemic Lupus Erythematosus-Associated Polyautoimmunity

Abstract: Introduction: Coexistence of more than one autoimmune disease (AD) in a single patient is known as polyautoimmunity, and may be seen in up to 35% of patients with ADs. The elimination of B-cells using Rituximab (RTX) improves clinical status in different ADs. The role of cytokine production by B-cells is unclear in systemic lupus erythematosus (SLE) and polyautoimmunity. Methods: As an exploratory study, plasma from 11 patients with either rheumatoid arthritis (RA) or SLE-associated polyautoimmunity was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 72 publications
1
0
0
Order By: Relevance
“…A study by Godsell et al involving 129 active SLE patients who underwent IL-10 examination at the first visit and continued 2 years later showed that serum IL-10 could be a predictive factor for the possibility of relapse in SLE patients. In the study, it was mentioned that patients with the highest quartile at the time of initial diagnosis of SLE had a 3.6-fold potential to experience active SLE in subsequent controls, and this result also correlated with SLE inflammatory markers such as erythrocyte sedimentation rate, anti-dsDNA, levels C3 and C4, and significant correlations were also obtained at the next SLE patient visit, so from this study it was seen that serum IL-10 levels might be a marker of disease activity in SLE patients [28], [29], [30].…”
Section: Discussionsupporting
confidence: 57%
“…A study by Godsell et al involving 129 active SLE patients who underwent IL-10 examination at the first visit and continued 2 years later showed that serum IL-10 could be a predictive factor for the possibility of relapse in SLE patients. In the study, it was mentioned that patients with the highest quartile at the time of initial diagnosis of SLE had a 3.6-fold potential to experience active SLE in subsequent controls, and this result also correlated with SLE inflammatory markers such as erythrocyte sedimentation rate, anti-dsDNA, levels C3 and C4, and significant correlations were also obtained at the next SLE patient visit, so from this study it was seen that serum IL-10 levels might be a marker of disease activity in SLE patients [28], [29], [30].…”
Section: Discussionsupporting
confidence: 57%